PENGARUH SANKSI PERPAJAKAN PENERAPAN E-FILING DAN SISTEM SELF ASSESMENT TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KECAMATAN SAGULUNG KOTA BATAM - Mortigor Afrizal Purba (JURNAL AKUNTANSI BARELANG, 2018)
Tax revenue is the safest and most reliable domestic revenue because it is flexible towards state income, and as an instrument for government to regulate the economy, which is easily influenced by conditions rather than non-tax state revenue.This study aims to determine the effect of self-assessment system of taxation sanctions and the application of e-filing to the compliance of individual taxpayers in Sagulung District,Batam City. The population in this study is an effective individual taxpayer registered in Sagulung District, Batam City, as many as 26.635. The sample used in this study were 394 respondents. The questionnaire data was tested with validity test and reliability test. The classic assumption test used is normality test, multicolinearity test, and heteroscedasticity test. Hypothesis test used is multiple linear regression test, t test and F test. All test using SPSS program version 22. The results showed that the self-assessment system significantly affects the compliance of individual taxpayers. Tax sanctions have a significant effect on individual taxpayer compliance. The application of e-filing does not significantly affects the compliance of individual taxpayers.